(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
In this work we will focus on the attire of the indigenous Patagonian women through documentary analysis (textual and graphic) and material record. Since it is the women who provide the clothes, their study will allow us to know one of the tasks that most demanded them. In addition, the manufacture, maintenance, and use of clothing involves a series of knowledge, tasks and various objects: technical procedures related to their production, social actors involved, provision of necessary raw materials, artifacts involved, spaces and times where the activities were developed, knowledge required, destination of the final product, knowledge transmission; age, sexual and social distinctions, and singularities that made the clothing the material and visual register of ethnic identity. Our objective in this work is to point out some of these characteristics of clothing, especially the latter, and examine the material record potentially attributable to the activities related to its preparation, use and disposal.